2010
DOI: 10.1177/1088357610377318
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Vocational Instruction Using Videotaped Modeling for Young Adults With Autism Spectrum Disorders Performing in Air-Inflated Mascots

Abstract: The authors examined the benefits of video modeling to teach a unique vocational skill set to an adolescent and two young adults with Autism Spectrum Disorders. Video modeling was used to teach skills necessary to entertain customers and promote products in a retail setting while wearing a WalkAround® costume. The three participants were observed before and after watching a video model perform the skills in the costume in scripted and naturalistic scenes. Data can be interpreted to conclude that all participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…Two studies used a combination of instruction, modeling, performance cue systems, and time delay prompting with graduated guidance (Burke et al 2010;Dotto-Fojut et al 2011). Pennington et al (2014) (Alexander et al 2013;Allen et al 2010aAllen et al , 2012Robinson and Smith 2010). Only one study assessed maintenance across a period of longer than 3 months (Dotson et al 2013).…”
Section: Impact Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies used a combination of instruction, modeling, performance cue systems, and time delay prompting with graduated guidance (Burke et al 2010;Dotto-Fojut et al 2011). Pennington et al (2014) (Alexander et al 2013;Allen et al 2010aAllen et al , 2012Robinson and Smith 2010). Only one study assessed maintenance across a period of longer than 3 months (Dotson et al 2013).…”
Section: Impact Studiesmentioning
confidence: 99%
“…Table 1 shows the type of employment-related skills that were targeted across the studies reviewed. Four studies taught participants the skill of wearing a "WalkAround" costume and promoting stores or entertaining customers (Allen et al 2010a(Allen et al , b, 2012Burke et al 2010). Photocopying skills were targeted in two studies (Bennett et al 2013c;Bereznak et al 2012), one of which also taught additional vocational skills of using a washing machine and making noodles (Bereznak et al 2012).…”
Section: Impact Studiesmentioning
confidence: 99%
“…All participants performed at a higher level than the benchmark that was set by researchers; indeed, participants recommended that other adults with ASD should try this training method (Allen et al, 2010;Kandalaft et al, 2012). Although the "video modeling" has proved to be effective, there are some operational problems, such as the limited number of participants and the fact that this type of training cannot secure a permanent employment position (Allen et al, 2010).…”
Section: Video Modelingmentioning
confidence: 99%
“…A number of studies looked into the advantages of the "video modeling" method as a means of vocational skill training (Allen, Wallace, Greene, Bowen, & Burke, 2010;Kandalaft, Didehbani, Krawczyk, Allen, & Chapman, 2012). The participants, in Allen et al's study, were an adolescent and two adults and the aim of the study was for them to wear a "walk-around costume" through which were shown various video clips teaching predefined skills.…”
Section: Video Modelingmentioning
confidence: 99%
See 1 more Smart Citation